Electrical energy production from plant biomass: an analysis model development for Pandanus Amaryllifolius plant microbial fuel cell - Teng Howe Cheng; Kok Boon Ching; Chessda Uttraphan; Yee Mei Heong (Institute of Advanced Engineering and Science, 2020)
Plant microbial fuel cell (P-MFC) is an electrochemical reactor that converts organic compounds to electrical energy through the catalytic reaction from electrochemically active bacteria (EAB). However, there is no sign of an attempt in developing the functional model in predicting the energy conversion and utilization of P-MFC. In this study, an analytic model is proposed to show the whole production process of the organic compound to electrical energy generation. Pandanus Amaryllifolius plant was used as sources of photosynthate, where biomass product from rhizodeposition, acetate was produced, and soil bacteria as the microbial culture, and air as the input to the cathode chamber. The proposed analytical model is able to predict the output of the P-MFC using the parameters from the experiment. The generated data from the model was then compared with the monitored data from the Pandanus Amaryllifolius P-MFC. The results show the electrical power output has a high similarity pattern with the bacterial growth curve model and able to achieve the coulombic efficiency of 95.32%.